Pengukuran Tingkat Efisiensi Pelayanan dengan Metode Data Envelopmenta Analysis (DEA) di PT Pos Indonesia Wilayah Surabaya Selatan - Rusindiyanto Rusindiyanto (Jurnal Aplikasi Manajemen, 2010)
Data of Envelopment Analysis (DEA) represent a[n important appliance able to be used to evaluate and improve; repair efficiency a[n effort service or manufacturing by measuring efficiency from a group of Decision Making Unit ( DMU) which of a kind. Target of this research to know service efficiency storey; level and factor - factor having an effect on to service efficiency in Post Of Fice Branch PT. Regional Post Indonesia [of] Surabaya South by using Data method of Envelopment Analysis (DEA), this Variable Research for example -Variable Input : Amount of Employees, Operating Expenses -Variable of Output : Earnings Of Stamp, Earnings Of Special Flash, Earnings Of Special Pareel Post Flash, Earnings Of Toll Money Order Post, Earnings Of Post of Express, Amount of Package and Amount Customer. Result of this research can be concluded can be concluded that efficient Post Of Fice Branch that is KPC Wonocolo, KPC Rungkut, KPC Ketintang and of KPC Hamlet Mussel, while KPC Compose Pilang and of KPC Wonokromo represent Post Of Fice Branch which is inefisien or is inefficient